Using Omaha System Documentation to Understand Physical Activity Among Rural Women - (:unkn) unknown (My University, 2015)
Rural women are more inactive and have different barriers to physical activity than those who live in more urban settings, yet few studies have specifically examined physical activity and associated factors in this population. Clinical data documented with standardized terminology by nurses caring for rural women may provide an opportunity to generate evidence that informs and improves nursing care. However, the knowledge to be gained and utility of nurses' clinical documentation in regard to physical activity have not been explored. Accordingly, the purpose of this study was to increase understanding of physical activity and associated factors among rural women by analyzing clinical data documented by local health department (LHD) nurses using the Omaha System standardized terminology. The study was guided by the ecological model for health promotion. A two-phase, retrospective, mixed-methods design was used. Phase One involved quantitative secondary analysis of a de-identified dataset derived from a convenience sample of women who received care from LHD nurses in a rural, Minnesota county (N=852). Measures included demographic data, baseline physical activity Knowledge, Behavior, and Status (KBS) ratings, physical activity signs/symptoms, and ecological factors operationalized with the Omaha System Problem Classification Scheme and Problem Rating Scale for Outcomes. Results revealed rural women had more than adequate Knowledge (M=3.41), inconsistent Behavior (M=3.27), and minimal to moderate signs/symptoms (M=3.56) for physical activity. Hierarchical regressions indicated ecological factors influenced physical activity behavior; however, age, BMI, and physical activity knowledge had more impact. Phase Two involved a focus group session with a purposive sample of LHD nurses (N=12) in the study setting. A semi-structured interview guide was used to elicit their perspectives about the quantitative findings. Three themes emerged with qualitative thematic analysis: (a) knowledge is good, behavior is the issue; (b) clients may be more complex than what is captured; and (c) assessment and coding are impacted by professional judgment, time constraints, and priorities. The outcomes of this study provide support for measuring and analyzing physical activity from an ecological perspective with clinical information documented by nurses using the Omaha System. The results indicate physical activity Behavior among rural, female, LHD clients in the Midwest is inconsistent and influenced by demographic factors of age, BMI, physical activity Knowledge, and environmental factors. However, LHD nurses perceive physical activity Behavior remains an issue, despite more than adequate physical activity Knowledge. In addition, nurses reported that documented data may not have fully captured client complexity due to nursing time constraints and client priorities. Future studies are needed with attention to these assessment and coding challenges. Providing nurses with ongoing education on KBS rating and information regarding potential research applications of client clinical data may help address these challenges and strengthen future research in this area.
Keywords: Ecological Theory; Local Health Department; Omaha System; Physical Activity; Rural Women